Pronunciation Typology of Consonant Sequences and Korean Language Education - Seonjung Kim (Acta Koreana, 2013)
This article aims to consider the pronunciation types of consonantal sequences, and to propose a teaching plan for Korean as a foreign language by taking advantage of them. The pronunciation of consonantal sequences is considered by dividing them into two groups; namely the case of no phonological changes such as Chinese and Vietnamese, and the case of consonantal assimilation such as Japanese, English, Hindi, and Korean. The consonantal assimilation is discussed in terms of the place of articulation and the manner of articulation. The former is quite common in languages, whereas the latter is not. Korean has both processes, even if the pronunciation with the application of place assimilation is not regarded as standard Korean. The consonantal assimilation in terms of manner of articulation in Korean appears to be nasalization and lateralization. Since the processes, both nasalization and lateralization, are marked compared to other languages, and the phonological environment of the two processes is so complex, Korean language learners may have some difficulty in the acquisition of Korean. Therefore, it is strongly recommended that teachers present the data which are involved with consonantal assimilation one by one, and provide explanations to the learners by contrasting the target language, Korean, and the learner’s native language. KCI Citation Count: 0